Influencing factors of new-onset diabetes after a renal transplant and their effects on complications and survival rate. - Chaoyang Lv (Public Library of Science (PLoS), 2014)
Objective To discuss the onset of and relevant risk factors for new-onset diabetes after a transplant (NODAT) in patients who survive more than 1 year after undergoing a renal transplant and the influence of these risk factors on complications and long-term survival. Method A total of 428 patients who underwent a renal transplant between January 1993 and December 2008 and were not diabetic before surgery were studied. The prevalence rate of and relevant risk factors for postoperative NODAT were analyzed on the basis of fasting plasma glucose (FPG) levels, and differences in postoperative complications and survival rates between patients with and without NODAT were compared. Results The patients in this study were followed up for a mean of 5.65 ± 3.68 years. In total, 87 patients (20.3%) developed NODAT. Patients who converted from treatment with CSA to FK506 had increased prevalence rates of NODAT (P <0.05). Multi-factor analysis indicated that preoperative FPG level (odds ratio [OR]  =  1.48), age (OR  =  1.10), body mass index (OR  =  1.05), hepatitis C virus infection (OR  =  2.72), and cadaveric donor kidney (OR  =  1.18) were independent risk factors for NODAT (All P <0.05). Compared with the N-NODAT group, the NODAT group had higher prevalence rates (P < 0.05) of postoperative infection, hypertension, and dyslipidemia; in addition, the survival rate and survival time of the 2 groups did not significantly differ. Conclusion Among the patients who survived more than 1 year after a renal transplant, the prevalence rate of NODAT was 20.32%. Preoperative FPG level, age, body mass index, hepatitis C virus infection, and cadaveric donor kidney were independent risk factors for NODAT. Patients who converted from treatment with CSA to FK506 after a renal transplant had aggravated impairments in glycometabolism. Patients with NODAT were also more vulnerable to postoperative complications such as infection, hypertension, and hyperlipidemia.